2012
DOI: 10.1037/a0026900
|View full text |Cite
|
Sign up to set email alerts
|

Use of slope and feature cues in pigeon (Columba livia) goal-searching behavior.

Abstract: Terrain slope provides a directional frame of reference for reorientation and navigation, similar to cardinal directions. Previous studies have shown that, in a goal location task, slope is a very salient cue and that pigeons tend to rely on it even if it is not the most informative cue. Such a strong dependence on one type of information, when there are more effective predictors of reward, is a key premise for a modular view of information processing. Here we tested the provocative hypothesis of a “slope modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Pigeons readily learned the reorientation task (Nardi, Mauch, Klimas, & Bingman, 2012). Post training tests indicated that the pigeons had encoded both cues.…”
Section: Slope Cues Versus Feature Cues In Pigeons and Peoplementioning
confidence: 99%
“…Pigeons readily learned the reorientation task (Nardi, Mauch, Klimas, & Bingman, 2012). Post training tests indicated that the pigeons had encoded both cues.…”
Section: Slope Cues Versus Feature Cues In Pigeons and Peoplementioning
confidence: 99%
“…However, for the first time in this series of experiments, slope failed to capture most of the associative strength, and pigeons chose almost equally the two correct corners (see Fig. 2; Nardi et al 2012). Nardi et al (2012).…”
mentioning
confidence: 79%
“…2; Nardi et al 2012). Nardi et al (2012). b Mean percentage of choices (± SEM) to each corner in the conflict test in Nardi et al (2012); overall, the two correct corners were chosen approximately equally Conclusions The finding from Nardi et al (2012) substantially weakens the claim of slope having a special status-driving searching behavior irrespective of other task--relevant cues.…”
mentioning
confidence: 88%
See 2 more Smart Citations